2003
DOI: 10.1097/00001665-200309000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Should Nevus Sebaceus of Jadassohn in Children be Excised? A Study of 757 Cases, and Literature Review

Abstract: The incidence of basal cell carcinoma and the need for prophylactic excision in children with nevus sebaceus of Jadassohn have been a topic of controversy. The authors performed a retrospective analysis of 757 cases from 1996 to 2002 in children aged 16 years or younger. No cases of basal cell cancer were found in the nevus sebaceus group. Recent studies in children corroborate these findings and question the need for prophylactic surgical removal of the nevus sebaceus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
79
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 7 publications
3
79
1
4
Order By: Relevance
“…In 1895, the German dermatologist Josef Jadassohn histologically described sebaceous nevus as a congenital facial or scalp lesion with excess glandular skin structures [2]. Sebaceous nevus of Jadassohn is a hamartoma and is often referred to in early reports as an organoid nevus (involving all skin layers) [3], and may contain a variety of excess cutaneous structures including pilosebaceous, eccrine and apocrine elements.…”
Section: Discussionmentioning
confidence: 99%
“…In 1895, the German dermatologist Josef Jadassohn histologically described sebaceous nevus as a congenital facial or scalp lesion with excess glandular skin structures [2]. Sebaceous nevus of Jadassohn is a hamartoma and is often referred to in early reports as an organoid nevus (involving all skin layers) [3], and may contain a variety of excess cutaneous structures including pilosebaceous, eccrine and apocrine elements.…”
Section: Discussionmentioning
confidence: 99%
“…Serious complications can occur such as the development of a secondary neoplasm and a risk of malignant transformation (6,12,13). Th e rate of malignancy remains unknown due a lack of prospective studies, but current literature suggests that the most common secondary neoplasms seen within sebaceous nevi are benign syringocystadenoma papilliferum and trichoblastomas (6,(13)(14)(15)(16)). Th ere is a known association with basal cell carcinomas, which have been reported to occur in <1% of patients with sebaceous nevi (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the overall risk of malignancy increasing with age, Rosen et al showed that basal cell carcinomas can develop within these lesions even prior to puberty and without signifi cant physical change (14). Conversely, Santibanez-Gallerani et al studied 757 cases of sebaceous nevi in children <16 years of age and found no basal cell carcinomas, thereby drawing the conclusion that prophylactic excision is not indicated (16). Determining workup and management of these lesions requires acknowledgment of these risks and consideration of patient goals.…”
Section: Discussionmentioning
confidence: 99%
“…2005 yılında 6264 çocuk arasında yapılan başka bir çalışmada 21 primer cilt tümörü arasında BCC insidansı %9.5 olarak belirtilmiştir (1). 2000 yılında yapılan başka bir çalışmada, 596 hastada (ortalama yaş:25.4) profilaktik nevus sebaseus eksizyonu sonrası 5 adet BCC tanı almıştır(%0.8) (9). 16 yaş altında sadece 6 hastada kitle içerisinde benign oluşum gözlenmiştir (9).…”
Section: Discussionunclassified
“…2000 yılında yapılan başka bir çalışmada, 596 hastada (ortalama yaş:25.4) profilaktik nevus sebaseus eksizyonu sonrası 5 adet BCC tanı almıştır(%0.8) (9). 16 yaş altında sadece 6 hastada kitle içerisinde benign oluşum gözlenmiştir (9). Premalign lezyon ve genetik hastalıklar dışında, çocukluk çağında BCC "de novo" olarak da ortaya çıkabilir.…”
Section: Discussionunclassified